A workflow for supporting the evolution requirements of RDF-based semantic warehouses. (18th May 2022) - Marketakis, Yannis; Tzitzikas, Yannis; Gentile, Aureliano; Niekerk, Bracken Van; Taconet, Marc
Semantic data integration aims to exploit heterogeneous pieces of similar or complementary information for enabling integrated browsing and querying services. A quite common approach is the transformation from the original sources with respect to a common graph-based data model and the construction of a global semantic warehouse. The main problem is the periodic refreshment of the warehouse, as the contents from the data sources change. This is a challenging requirement, not only because the transformations that were used for constructing the warehouse can be invalidated, but also because additional information may have been added in the semantic warehouse, which needs to be preserved after every reconstruction. In this paper, we focus on this particular problem using a semantic warehouse that integrates data about stocks and fisheries from various information systems, we detail the requirements related to the evolution of semantic warehouses and propose a workflow for tackling them.